Comparative Effects of Enoxaparin and Heparin on Arterial and Venous Clot Lysis with Alteplase in Dogs - Stassen, Jean-Marie; Rapold, Hans J; Vanlinthout, Ingrid; Collen, Désiré (Thrombosis and Haemostasis, 1993)
The effects of Enoxaparin with a specific anti-thrombin (anti-IIa) activity of 32 U/mg and a specific anti-factor-XA (anti-Xa) activity of 96 U/mg, and of heparin with a specific anti-IIa and anti-Xa activity of 192 U/mg, on thrombolysis with alteplase (Actilyse®) were compared in a randomized blinded study using a combined arterial and venous thrombosis model in the dog. All dogs received an intravenous bolus of 5 mg/kg lysine-acetyl salicylate and 0.5 mg/kg alteplase over 60 min. Twenty-eight dogs were randomly assigned to seven treatment groups: placebo, Enoxaparin 1.5, 3 or 6 mg/kg, or heparin 0.5, 1 or 2 mg/kg, given as a 50% intravenous bolus and a 50% infusion over 2 h. Steady-state plasma levels ranged from 0.37 to 1.0 anti-IIa U/ml and 0.9 to 3.1 anti-Xa U/ml for Enoxaparin and from 0.4 to 2.3 anti-IIa U/ml and 0.42 to 3.2 anti-Xa U/ml for heparin. The activated thromboplastin time with 6 mg/kg Enoxaparin prolonged to 94 ± 19 s and with 2 mg/kg heparin to >150 s.The time to reflow was 120 ± 36 min with placebo, 19 ± 5 min with 6 mg/kg Enoxaparin (p = 0.03 vs control), and 22 ± 5 min with 2 mg/kg of heparin (p = 0.03 vs control). Arterial patency, expressed in min reflow during the 180 min observation period correlated significantly with the dose of anticoagulant given (r = 0.73, p = 0.003 for Enoxaparin and r = 0.61, p = 0.012 for heparin). When the dose of anticoagulant was expressed in anti-IIa U/kg, Enoxaparin was significantly more potent than heparin (patency times of 0.62 ± 0.15 and 0.21 ± 0.09 min per anti-IIa U/kg respectively, p = 0.04) but in terms of mg/kg or anti-Xa U/kg both anticoagulants were equipotent.Venous clot lysis also correlated significantly with the dose of anticoagulant given (r = 0.62, p = 0.011 for Enoxaparin and r = 0.76, p = 0.004 for heparin). When the dose of anticoagulant was expressed in anti-IIa U/kg Enoxaparin was equipotent to heparin, but in terms of mg/kg or anti-Xa U/kg heparin was more potent than Enoxaparin (6 ± 2% lysis per mg/kg Enoxaparin and 35 ± 9% lysis per mg/kg heparin, p= 0.001).In conclusion, Enoxaparin and heparin enhance arterial and venous clot lysis with alteplase differently; for arterial patency, potency correlates with anti-Xa activity whereas for venous clot lysis potency correlates with anti-IIa activity.